Mareva Injunction: history developments and application / Bunsi Kasin - Kasin, Bunsi (Faculty of Law, 1987)
The importance and the effectiveness of Mareva injunction was put to test in Malaysia in 1984 and 1985 subsequent to its emergence in 1982. This arose from the BMF scandal; the biggest financial scandal in the country to date. The Mareva injunction was granted to freeze all the movable and immovable assets alike of the parties involved. To quote "The Star" dated Saturday, Harch 28, 1987 entitle "Hashim agrees to return more than $120 million"; "It was ordered that the Mareva injunction which the court granted on Jan, 16, 1985, freezing Datuk Hashim's assets continue to remain in force until full realisation of the money involved" The aim of this paper has three folds: 1. to study the history of the law prior to and subsequent to Mareva injunction; 2. to evaluate the development of Mareva injunction through decided cases; and 3. to layout the various factors that the parties concerned must comply with before the Mareva injunction can be granted and the parameter of the Court's jurisdiction.